EVALUASI PENERAPAN SISTEM INFORMASI AKUNTANSI PENERIMAAN KAS ORGANISASI NIRLABA (Studi Kasus pada Lembaga Amil Zakat Nasional Nurul Hayat Cabang Solo) - Ayu Muslikhah Perdana Wati, Djoko Kristianto & Muhammad Rofiq Sunarko (Universitas Slamet Riyadi, 2017)
The purpose of this study were: 1) to analyze the application of cash receipts accounting information systems used at the Institute for National Zakat (LAZNAS) Nurul Hayat Solo. 2) analyze the application of accounting information systems on a cash receipts LAZNAS Nurul Hayat Solo are in accordance with Statement of Financial Accounting Standards (SFAS) No. 109. The method using the case study method, the type of data used quantitative and qualitative data. Data collection methods used documentation, observation and interviews. Data analysis technique used is descriptive qualitative analysis. Based on the results of research and discussion, the researchers conclude that LAZNAS Nurul Hayat Solo in applying accounting information system of cash receipts are in accordance with Statement of Financial Accounting Standards (SFAS) No. 109. This is indicated by: 1) In the process of acceptance and distribution of zakat funds and funds donation / charity LAZNAS Nurul Hayat Solo recorded as increase and decrease during the zakat zakat funds received and expended. 2) LAZNAS Nurul Hayat Solo in preparing the present keuangnnya every transaction separately based on the source and uses. 3) Overall financial reports LAZNAS Nurul Hayat Solo in accordance with SFAS No. 109 of the recognition and measurement as well as the overall presentation uan in accordance with the provisions of SFAS No. 109.Keywords: Accounting Information Systems, Cash Receipts, Nonprofits